Current status of Harmful Termites (Isoptera) in Hoi An Ancient Town and Effectiveness of Control of Main Harmful Coptotermes with Bait BDM 10 - Huy, Nguyen Quoc (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
The results of investigations and assessments about termites damagging 178 buildings in the Hoi An ancient town identified 6 species of 2 genera and 2 families. In which, Coptotermes was dominant genus with 4 species, and Cryptotermes had 2 species. There were 102/178 investigated buildings being invaded by termites with various levels. There were 4 species identified as major pests for the Hoi An ancient town. The most dangerous termite species for building was Coptotermes gestroi, followed by Coptotermes formosanus, C. ceylonicus and Cryptotermes domesticus . 77 works which were invaded by Coptotermes had been treated with BDM10 bait. The results showed that the efficiency of termite treatment reached 100% in all of works, in which: 78.11% of the works had achieved the control effect just for the first treatmen; 19,39% of the works needed to be treated for the second time and only 2.5% of the works that were severely damaged, needed  the third time for control with bait.